Textual Error Meaning in English to Indonesian Translation of EFL Class - Subandowo, Dedy; Faliyanti, Eva; Triatmi, Yuli (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2019)
This research addresses on textual error meaning of English to Indonesian translation in EFL class. This study is aimed to describe the frequency of error distribution and to investigate the dominant errors made by students in English to Indonesian Translation. The subject of this research is the fourth-semester English education students at the Muhammadiyah University of Metro. There are 37 students used as the total sampling technique to get the sample. To collect the data, the writer used a test as the instrument, i.e. an essay test. The collected data are analyzed by means of error analysis which starts from collecting the data, identifying the errors from the answer sheet, classifying and describing of errors on each type and finally tabulating the students' errors. The finding shows that frequency of errors made by the student in translating English into Indonesian can be classified into 73.43% of verb, 85% of noun, 52.7% of adverb and 100% of conjunction. On the other hand, the common error in translating textual meaning occurs in conjunction class which the average is 100%. It is the biggest percentage of all the errors which is automatically be the dominant error of textual meaning in this research